2021
DOI: 10.1111/1756-185x.14257
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphisms of SIRT1 in patients with rheumatoid arthritis

Abstract: Aim Previous studies have shown that silent information regulator 1 (SIRT1) expression is elevated in rheumatoid arthritis (RA) patients. However, whether gene polymorphisms in SIRT1 gene associated with RA in a Chinese Han population remains to be discussed. Method In this case‐control study, 529 RA patients and 700 healthy controls were selected, and association of 11 SIRT1 gene polymorphisms (rs12415800, rs3740051, rs932658, rs3740053, rs7895833, rs10509291, rs33957861, rs7069102, rs2273773, rs3818292, rs14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Similarly, resveratrol improved arthritis scores and reduced incidence in the CIA model—both in preventive and therapeutic mode—by inhibiting Th17 and B cell function 63 . Furthermore, a recent study also identified gene polymorphisms of SIRT1 in RA patients 64 .…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, resveratrol improved arthritis scores and reduced incidence in the CIA model—both in preventive and therapeutic mode—by inhibiting Th17 and B cell function 63 . Furthermore, a recent study also identified gene polymorphisms of SIRT1 in RA patients 64 .…”
Section: Discussionmentioning
confidence: 96%
“…However, several points need to be further discussed in the future. First, it is accepted that genetic mutation may affect mRNA expression of a gene, which will then change protein expression ( 225 , 226 ). Therefore, IL-27 gene polymorphisms may indeed change the mRNA and protein expression of IL-27, which is involved in the pathogenesis of different autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 expression in the joint tissues of RA patients is obviously higher than that of general healthy population, and this abnormality positively correlates to RA severity. 28 , 29 As such, whether SIRT1 deficiency is common under RA conditions needs to be further validated. Successfully answering this question is important for the development of SIRT1-targeting anti-rheumatic therapies.…”
Section: Discussionmentioning
confidence: 99%